Implementation Of School Security Patrol (SSP) Activities In Developing Character Education - Rohimah; Agus Setyawan; Nisfi Dahnia (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The School Security Patrol activities at SDN Jaticempaka VI Bekasi showcase the school’s dedication to creating a secure and positive learning environment, emphasizing character development. The program involves students actively engaging in security responsibilities, fostering values like responsibility, leadership, cooperation, and community spirit. This integration aligns with the broader goal of character education, aiming to nurture students academically, ethically, and socially. SDN Jaticempaka VI Bekasi’s proactive approach combines security measures with character development, highlighting its commitment to shaping well-rounded individuals for success. The study aims to explore the implementation model, the role in national character development, and obstacles faced by the School Security Patrol activities at SDN Jaticempaka VI Bekasi. Findings reveal that the program is executed by class representatives following a set schedule. The role of the school security patrol in character development is crucial, instilling values such as courage, discipline, independence, responsibility, and social concern. However, obstacles include a lack of professional trainers, members not fulfilling duties due to unexpected absences, and student indifference towards patrol members. Final Conclusion is show that, SDN Jaticempaka VI Bekasi’s School Security Patrol activities effectively combine security and character development, contributing to a holistic educational experience. Despite facing challenges, the program’s positive impact on students’ character underscores the school’s commitment to nurturing well-rounded individuals.